Sharing ecological wisdom through dialogue across worldview boundaries - Peter A. Raine (Environmental Association of Southern Africa, 1998)
This paper aims to build a bridge between worldviews, a bridge capable of connecting what are often incomensurable perceptions of environmental issues. A model for communication which goes beyond argumentation and dialectics is derived and outlined from the various works of Raimon Panikkar. Panikkar's diatopical model offers symbolic discourse as a means to link theological, philosophical, and ecological aspects of environmental issues. The example of Fijian rainforest conservation is used to show how ecological wisdom may be exchanged across worldview boundaries.